المراقبة و التدقيق في البنوك - قدور, نوال (My University, 2021)
Commercial Banks are consideredamongthe most important institutions on which the economies of countries are based, as the bankIs the effective unit for the development and development of the economy, by achieving certain goals by developingbankingmethods and operationsusingfinancial and humanresources, and then the continuation of the bank„s life for a longer period and in more efficient ways, by creatingsystems and methods It helps in the continuity of the bank and in dealingwithrisks and evenavoidingthem, including the processes of control and auditing Sinceourstudyisbased on the effectiveness of the control and audit system at the level of banks to follow up the operationscarried out by banks and to ensure good conduct and the detection of fraud and manipulation known in addition to identifying how to grant and manage loans and try to find out the extent of congruence between the theoretical and realisticside, wherewedividedourworkinto A theoretical part consisting of twochapters and an applied part to study the case of granting and managingloans in the Agency of the Local Development Bank in Mostaganem “BDL”.
وكالة بنك التنمية المحلية BDL
Keywords: Bank, audit, control, loans